Storage Changes Stable Isotope Composition of Cucumbers - Horacek, Micha; Papesch, Wolfgang (Frontiers in Sustainable Food Systems, 2021)
Vegetable food stuff produced under controlled and identical conditions from one farm of identical “age” (batch) has a similar isotopic composition. This fact can be used to control the origin of vegetables. This question is of special relevance when food-contaminations have to be traced back to the producer, or certain production claims have to be controlled. However, as vegetables are harvested, brought to whole-sale merchants and to retail shops, where they remain until being bought by the consumer, one has to consider possible changes in isotopic composition during this transfer period, when comparing vegetables of questioned origin with reference samples taken directly from the field/producer. We investigated changes in the isotope composition of vegetables during storage by studying as an example cucumbers from one batch. We stored the cucumbers in a vegetable storage under controlled conditions and removed one sample every day and analyzed its isotopic composition. We found changes in the δ15N and δ18O isotope values over the investigated period of 21 days, with both parameters showing positive linear correlations, and maximum enrichments with time of more than 1.5‰ for δ15N and more than 2‰ for δ18O. However, within the interval the samples remained in a saleable condition the isotope variations remained more or less within the variability of the sample batch. Our study demonstrates that changes in the isotopic signature in vegetables might occur after harvest during storage and have to be taken into account when (commercial) samples collected in a market are investigated.